Rhodium diamidobenzene complexes: a tale of different substituents on the diamidobenzene ligand - Suhr, Simon; Walter, Robert; Beerhues, Julia; Albold, Uta; Sarkar, Biprajit (Chemical science (Cambridge), 2022)
Diamidobenzene ligands are a prominent class of redox-active ligands owing to their electron reservoir behaviour, as well as the possibility of tuning the steric and the electronic properties of such ligands through the substituents on the N-atoms of the ligands. In this contribution, we present Rh( iii ) complexes with four differently substituted diamidobenzene ligands. By using a combination of crystallography, NMR spectroscopy, electrochemistry, UV-vis-NIR/EPR spectroelectrochemistry, and quantum chemical calculations we show that the substituents on the ligands have a profound influence on the bonding, donor, electrochemical and spectroscopic properties of the Rh complexes. We present, for the first time, design strategies for the isolation of mononuclear Rh( ii ) metallates whose redox potentials span across more than 850 mV. These Rh( ii ) metallates undergo typical metalloradical reactivity such as activation of O 2 and C-Cl bond activations. Additionally, we also show that the substituents on the ligands dictate the one versus two electron nature of the oxidation steps of the Rh complexes. Furthermore, the oxidative reactivity of the metal complexes with a [CH 3 ] + source leads to the isolation of a unprecedented, homobimetallic, heterovalent complex featuring a novel π-bonded rhodio- o -diiminoquionone. Our results thus reveal several new potentials of the diamidobenzene ligand class in organometallic reactivity and small molecule activation with potential relevance for catalysis. Diamidobenzene ligands are versatile platforms in organometallic Rh-chemistry. They allow the isolation of tunable mononuclear ate-complexes, and the formation of a unprecedented homobimetallic, heterovalent complex.